Economic notes: The early years, 1972–1983. (1st February 2023) - Asso, Pier Francesco; Ferri, Giovanni
Abstract: We set the stage in 1972 when the bank Monte dei Paschi di Siena founded Economic Notes as part of its manifold scheme to reach two main goals: going international and acquiring a stronger position in the public discourse on economics and finance. Then, we highlight how the new Journal aimed at achieving Monte's goals by adopting a specific editorial style. Moreover, through the turmoil of its first dozen years, Economic Notes ' bold strategy attracted top international authors and testimonials, selected topical issues, knitted theory and policy, embraced pluralist and forward‐looking views, helped the University of Siena to strengthen its international connections. The Journal quickly became a landmark for domestic, European and global debates owing also to favourable contingencies. A special blessing was that, would be Nobel laureate, Bob Mundell had just settled down in a shabby villa in the outskirts of Siena where he organized the Santa Colomba Meetings. Those informal summer workshops brought a free flow of the most authoritative experts on international money and finance exactly at the time the Bretton Woods monetary order collapsed and stagflation risks emerged. That greatly favoured the editorial success of the Journal throughout the 1970s.